Interpretation of the Quran by the Quran in Adwaa al-Bayan wal Mizan: A Comparative study - Al-Kilani, Omar Abdullah Najmuddin (Al-Adab Journal, 2019)
Belief in an approach stems from the full conviction of all the details of that chosen approach of interpretation, and definitely, it is one of the most complex interpretative steps. Here lies the importance of studying the various interpreters' approaches, each of which flows on the river of the Holy Quran and its grandeur and supremacy. But these approaches are too diverse to be fully understood. That is why the approach of interpreting the Quran by the Quran is selected. This is the interpretation of Sheikh Al-Chinguetti , known as Adwaa al-Bayan wal Mizan in the Clarification of the Qur'an by the Qur'an and the interpretation of Tabatabai known as the Al-Mizan in the Interpretation of the Qur'an by introducing the authors of both interpretations, clarifying their approaches, styles and their methods, comparing both interpretations through some examples of ayas interpreted according to the approach of the interpretation of the Holy Qur'an by the Quran.